1993
DOI: 10.1002/j.1460-2075.1993.tb06112.x
|View full text |Cite
|
Sign up to set email alerts
|

A human homologue of Saccharomyces cerevisiae SNF2/SWI2 and Drosophila brm genes potentiates transcriptional activation by the glucocorticoid receptor.

Abstract: Several of the SNF and SWI genes of Saccharomyces cerevisiae code for proteins believed to assist transcriptional activators by relieving nucleosome repression. One of these proteins, SNF2/SWI2, has a homologue in Drosophila, a regulator of homeotic genes known as brahma or brm. In this report, we show that a counterpart of SNF2/SWI2 also exists in mice and humans. The human protein, designated hbrm, is a 180 kDa nuclear factor that can function as a transcriptional activator when fused to a heterologous DNA b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
493
2
17

Year Published

1998
1998
2007
2007

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 567 publications
(521 citation statements)
references
References 73 publications
7
493
2
17
Order By: Relevance
“…This motif was ®rst described following the cloning of the brahma (brm) gene in drosophila (Haynes et al, 1992;Tamkun et al, 1992) and has since been identi®ed in other transcriptional co-activators including the human brahma protein, BRM (Muchardt and Yaniv, 1993) and the yeast protein SNF2/SWI2 (Laurent et al, 1993). The cell cycle gene 1 (CCG1) (Sekiguchi et al, 1991) which was later identi®ed as hTAF II 250 (Hisatake et al, 1993;Ruppert et al, 1993) and shown to be necessary for G1 progression in mammalian cells also contains a bromodomain.…”
Section: Discussionmentioning
confidence: 99%
“…This motif was ®rst described following the cloning of the brahma (brm) gene in drosophila (Haynes et al, 1992;Tamkun et al, 1992) and has since been identi®ed in other transcriptional co-activators including the human brahma protein, BRM (Muchardt and Yaniv, 1993) and the yeast protein SNF2/SWI2 (Laurent et al, 1993). The cell cycle gene 1 (CCG1) (Sekiguchi et al, 1991) which was later identi®ed as hTAF II 250 (Hisatake et al, 1993;Ruppert et al, 1993) and shown to be necessary for G1 progression in mammalian cells also contains a bromodomain.…”
Section: Discussionmentioning
confidence: 99%
“…The reversible epigenetic silencing of BRM S Glaros et al SWI/SNF activity (Muchardt and Yaniv, 1993;Trotter and Archer, 2004). We used a subline of the BRG1/ BRM-deficient SW13 cell line, MG2-13, into which a glucocorticoid-responsive MMTV-luciferase (MMTVluc) reporter was stably introduced.…”
Section: Temporal Effects Of Hdac Inhibitors On Brm Reexpressionmentioning
confidence: 99%
“…The glucocorticoid dexamethasone cannot induce luciferase activity unless BRG1 function, and hence SWI/SNF complex activity, is restored in these cells (Trotter and Archer, 2004). To determine whether, like BRG1, ectopic BRM expression can also induce luciferase activity, we introduced BRG1, BRM or their dominant-negative isoforms (dnBRG1 or dnBRM) (Khavari et al, 1993;Muchardt and Yaniv, 1993) into these reporter cells. Transient transfection of BRM but not dnBRM allowed dexamethasone to significantly induce luciferase activity (Figure 2a), a finding in agreement with previous work by Muchardt and Yaniv (1993) and Bourachot et al (2003).…”
Section: Temporal Effects Of Hdac Inhibitors On Brm Reexpressionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, the precise in vivo functions of the complexes which contain ISWIp are unknown. Humans have at least two SNF2/SWI2 homologues: hBRM (human brahma or hSNF2␣) and BRG1 (brahma-related gene 1 or hSNF2␤) (Muchardt & Yaniv 1993;Khavari et al 1993;Chiba et al 1994). The products of both genes are also components of 2-MD protein complexes and are implicated in transcriptional activation by the glucocorticoid receptor and growth control through Rb (Muchardt & Yaniv 1993;Chiba et al 1994;Dunaief et al 1994;Muchardt et al 1995;Singh et al 1995;Strober et al 1996;Wang et al 1996a).…”
Section: Introductionmentioning
confidence: 99%